Răspunsuri

2014-03-06T13:57:23+02:00
2x + 3y = 48
x * 0,2 = y * 0,5 = k
x * 0,2 = k => x = k/0,2 = 15
y * 0,5 = k => y= k/0,5 = 6

2* k/0.2 + 3* k/0,5 = 48
amplificam fractia 2k/0,2 cu 5 iar fractia 3k/0,5 cu 2 =>
10k + 6k = 48
16k = 48
k= 48/16
k=3
14 4 14
2014-03-06T14:49:06+02:00
2x + 3y = 48
x * 0,2 = y * 0,5 = k
x * 0,2 = k => x = k/0,2 = 15
y * 0,5 = k => y= k/0,5 = 6

2* k/0.2 + 3* k/0,5 = 48
amplificam fractia 2k/0,2 cu 5 iar fractia 3k/0,5 cu 2 =>
10k + 6k = 48
16k = 48
k= 48/16
k=3
12 4 12